ANALYSIS OF CORROSION RATES ACROSS VARIOUS WATER DEPTHS IN MALAYSIA TOWARDS THE IMPACT OF INTEGRITY ON OFFSHORE STRUCTURE - Wee Yeong, Brennan Xiang (Universiti Teknologi PETRONAS, 2020)
In the oil and gas industry, many fixed offshore platforms have been constructed in Malaysia. These offshore platforms are unique structures and the main function are to hold industrial equipment that services oil and gas production and drilling. However, some of these offshore platforms are operating beyond their design life and are susceptible to various loads from the environments and eventually causing structural failure. It has been recognized that corrosion is one of the worst threats to the offshore platforms as it tends to corrode the structure and weaken the structure them resulting in the increase of likelihood of a failure to happen. Additionally, the corrosion rate might also vary from areas to areas and from depths to depths. From the scope, an adequate offshore jacket platform was selected as the main source of study. In this case, platform A, an asset from PETRONAS located in Sabah water is chosen. Therefore, in this study, the review of these corrosion rate in various depth towards the overall integrity of the structure.